LEADERSHIP OF MADRASAH SUPERVISORS IN SUPPORTING MADRASAH QUALITY CULTURE IN KUPANG CITY - Umar Ali (Program Studi PGSD Universitas Flores, 2025)
One of the key challenges hindering the improvement of educational quality in Kupang City is the prevalence of a weak quality culture within madrasahs. This study aims to examine the role of madrasah supervisors’ leadership in fostering and strengthening a culture of quality within the madrasah environment. Data were collected using in-depth interviews, participatory observation, and document analysis involving supervisors, madrasah principals, and teachers. To enhance the validity of the findings, data triangulation was employed. The findings of the study reveal that madrasah supervisors employ transformational leadership strategies characterized by participatory supervision, continuous mentoring, and efforts to enhance teacher competencies. These strategies have a positive impact on improving educator professionalism, fostering a collaborative work culture, and increasing parental and community involvement in the educational process. Despite various challenges, including limited resources, varying levels of commitment, and complex socio-cultural contexts, supervisory leadership continues to play a significant role in fostering a sustainable quality culture within madrasahs. The study concludes that collaborative, learning-centered leadership is essential for systematically and contextually strengthening the quality culture in madrasah education.